Report on the third UNCTAD public symposium : making trade and finance work for people and the planet (UN New York, 2011)
Presents the report on the discussions to make trade and finance work for full and productive employment and to reduce inequalities; the financial and monetary reforms necessary to ensure sustainable economic growth and how the transition to a green economy could be fair and equitable.
Keywords: INTERNATIONAL TRADE